Giving Lemon Aroma Therapy to the Frequency of Emesis Gravidarum in First- Trimester Pregnant Women - Prihartini, Ade Rahayu; Agustina, Ely Eko; Sari, Ossie Happina; Khaeriyah, Hana Nurul (Yayasan Ahmad Mansyur Nasirah, 2024)
One of the discomforts experienced by pregnant women in the first trimester of pregnancy is feeling nausea and vomiting as one of the symptoms of Emesis Gravidarum. The World Health Organization (WHO) states that hypermesis gravidarum occurs worldwide, with a prevalence of 78.5% of all pregnancies. One therapy that is safe and can be given to pregnant women who experience nausea and vomiting is lemon aromatherapy. This study aims to determine the effect of giving lemon aroma therapy on the frequency of emesis gravidarum (nausea and vomiting) in first trimester pregnant women. This study used a quasi-experimental method with a two-group pretest-posttest design. The population in this study were all first trimester pregnant women in the Kedawung Health Center Working Area, totaling 40 pregnant women. The sample used in this study was 38 respondents who were taken using purposive sampling technique. Data analysis techniques used in this study were univariate and bivariate analysis. The chi square test was used in this study in analyzing bivariate to test the hypothesis of this study. The results showed there was a significant decrease in the frequency of emesis gravidarum before and after the use of lemon aroma therapy with a p-value of 0.008. Giving aroma therapy to pregnant women can reduce the frequency of Emesis Gravidarum in the first trimester. It is recommended for pregnant women to use lemon aroma therapy in overcoming emesis gravidarum (nausea and vomiting).